COMPARATIVE STUDY OF PAP SMEAR AND COLPOSCOPIC FINDINGS IN PATIENTS WITH VAGINAL DISCHARGE ATTENDING OPD IN TERTIARY CARE CENTRE - Dr. Swati Bulbul; Dr. Ranjan Kumari; Dr. Homa Imam (Student's Journal of Health Research, 2023)
Background: The cervix, which has an exterior and internal os, is the lower, narrower part of the uterus. The location of the squamocolumnar junction, which connects the squamous and glandular epithelium, varies with age and hormonal influence. The columnar epithelium is located close to the external os when young. After breast cancer, cervix cancer is the second most prevalent cancer. Aim and Objective: To determine the prevalence of precancerous lesions in the study population, to screen patients with abnormal vaginal discharge with pap smear and colposcopy, and to screen patients with abnormal vaginal discharge with colposcopy. Methods: The study was carried out in the Obstetrics and Gynaecology Outpatient Department of Jawahar Lal Nehru Medical College and Hospital, Bihar, India. Women in the outpatient section of Obstetrics and Gynaecology between the ages of 35 and 55 were included. A Colposcopy and a Pap smear were performed on each individual. Results: In this study, when the cervix was seen through a speculum and a pap smear was collected, the majority of the study population- 52% (13/25)- had mucopurulent discharge. 8% (2/25) had blood-stained discharge, 16% (4/25) had greenish discharge, and 32% (8/25) had a thick, curdled-white discharge. All patients in our study had pap smears collected, and 40% (10/25) of those smears were HSIL, 28% (7/25) were LSIL, 32% (8/25) were inflammatory smears, 405 (10/25) were ASCUS, 8% (2/25) were normal, and 4% (1/25) were adenocarcinomas. Conclusion: Colposcopy is a screening method that can be used to find precancerous lesions. Compared to a Pap smear, colposcopy offers higher sensitivity and accuracy in detecting CIN. CIN must be identified earlier. Colposcopy is a screening method that can be used to find precursor lesions for cancer. The sensitivity of colposcopy is high Pap smears lack the speed and accuracy needed to detect CIN.